EFFECTIVENESS OF THE USE OF COMPUTER MULTIMEDIA AND GROUP DISCUSSION ON LEARNING OF BRAKE SYSTEM CLASS XI TEKNIK KENDARAAN RINGAN SMK TAMAN KARYA MADYA TEKNIK KEBUMEN ACADEMIC YEAR 2014/2015 - Wiwit Winarko; Subagyo Subagyo (Jurnal Taman Vokasi, 2015)
The purpose of this study was to determine (1) the effectiveness of the use of computer multimedia on learning brake system and (2) the effectiveness of the use of group discussion method on learning the brake system Class XI Teknik Kendaraan Ringan SMK Taman Karya Madya Teknik Kebumen in the academic year 2014/2015. This study classified the type of experiment research. Data collection techniques using documentation techniques and test . Instrumen this study is a test. Data analysis method used descriptive method and hypothesis test using t test, which precededÂ  test of analysis requirementsÂ  is test of normality and homogenity. The results showed that (1) there is a significant effectiveness in the use of multimedia computer learning the brake system at a price of tobt = 6.003 and the value of significance 0.00 <0.05 and (2) there is a significant effectiveness of the use of the method of discussion groups on learning the brake system with prices tobt = 4.105 and the value of significance 0.00 <0.05. thus, the average value of the average learning outcomes brake system using computer multimedia 14.55 and the average value oflearning outcomes brake system using group discussion of 13.50. Based on the average value, it can be concluded that the use of computer multimedia more effective than the use of group discussion method on learning the brake system.